Synthesis and mechanistic study of in situ halogen/nitrogen dual-doping in graphene tailored by stepwise pyrolysis of ionic liquids - Park, Ok-Kyung; Kim, Hyun Joo; Hwang, Jun Yeon; Lee, Dong Su; Koo, Jahyun; Lee, Hoonkyung; Yu, Jong-Sung; Ku, Bon-Cheol; Lee, Jae Kwan (IOP PUBLISHING LTD, 2015)
New halogen/nitrogen dual-doped graphenes (X/N-G) with thermally tunable doping levels are synthesized via the thermal reduction of graphite oxide (GO) with stepwise-pyrolyzed ionic liquids. The doping process of halogen and nitrogen into the graphene lattice proceeds via substitutional or covalent bonding through the physisorption or chemisorption of in situ pyrolyzed dopant precursors. The doping process is performed by heating to 300-400 degrees C of ionic liquid, and the chemically assisted reduction of GO is facilitated by ionic iodine, resulting in I/ N-G materials possessing about three and two orders of magnitude higher conductivity (similar to 22 200 S m(-1)) and charge carrier density (similar to 1021 cm(-3)), compared to those of thermally reduced GO. The thermally tunable doping levels of halogen in X/N-G significantly increase the conductivity of doped graphene to similar to 27 800 S m(-1).
Keywords: NITROGEN